Complexity and formative experiences - Roque Strieder; Clenio Lago; Paulino Eidt (Universidade Federal de Santa Catarina, 2017)
The contemporaneity is characterized by instability and diversity calling into question certainties and truths proposed in modernity. We recognize that the reality of things and phenomena become effective as a set of events, interactions, retroactions and chances. This different frame extends the need for revision of the epistemological foundations that sustain educational practices and give them sense. The complex thinking is an alternative option for acting as a counterpoint to classical science and its reductionist logic and knowledge compartmentalization, as well as to answer to contemporary epistemological and educational challenges. It aims to associate different areas and forms of knowledge, without, however merge them, distinguishing without separating the several disciplines and instances of the realities. This study, in theoretical references, highlights the relevance of complex approaches to support formative experiences because also able to produce complexities in reflections about educational issues. We conclude that formative possibilities from complexity potentialize the resignification of human's conception and the understanding of its singularity in interdependence; The understanding that pedagogical and educational activities is a constant interrogation about the possibilities of knowing the knowledge and reframe learning, far beyond knowing its functions and utilitarian purposes; and, as a formative possibility, places us on the trail of responsibility, not as something eventual, but present and indicative of freedom to choose to stay or go beyond.